Glycerol etherification towards selective diglycerol over mixed oxides derived from hydrotalcites: effect of Ni loading - Alouini, Mohamed-Slim; Cecilia-Buenestado, Juan Antonio; Ghorbel, S.B.; Saïd, Zina; Rodríguez-Castellón, Enrique; Moreno-Tost, Ramón (Springer Nature, 2021)
A series of tetrametallic hydrotalcite with different Ni loading, were synthesized by coprecipitation method. Then, these hydrotalcites were calcined in their respective metal oxides and were used as catalysts in the etherification reaction for the synthesis of polyglycerols. The effect of Ni loading on the structural and textural features was investigated by various techniques such as X-ray diffraction (XRD), thermogravimetric analysis TG–DSC–MS, temperature-programmed reduction (H2-TPR), temperature-programmed desorption (NH3-TPD) and 1-butene isomerization as a model reaction to probe acid–base character of catalysts. Mixed oxides derived from hydrotalcites are found to be active and suitable, via solvent free, in the glycerol etherification reaction. A gradual enhance of glycerol conversion is revealed when increasing the Ni/Mg molar ratio and the most active catalyst found is HTc-Ni75% with full selectivity to diglycerol.
Keywords: Alcoholes; Catalizadores; Hydrotalcite; Etherification; Glycerol; Diglycerol; Biodiesel